The 2015 ENFSI Fingerprint Working Group testing programme. (November 2017) - Mattei, A.; Fish, J.; Hilgert, M.; Lövby, T.; Svensson, M.; Vaughan, J.; Zampa, F.
Highlights: Three collaborative exercises were carried out in 2015 within ENFSI EFP-WG. Visualisation Test: there is a need for consistent samples. Imaging Test: a reference procedure is necessary. Individualisation Test: 5 false positive results. A common denominator to define a minutia and the "quality" of a mark is necessary. Abstract: As early as 2004, the Fingerprint Working Group (EFP-WG) of the European Network of Forensic Science Institutes (ENFSI) has organised proficiency tests (PT's), as well as collaborative exercises (CE's), as a way of raising standards within the fingerprint profession. This article provides an overview of the three collaborative exercises carried out in 2015. The characteristics of the testing programme are summarised, followed by an overview of the knowledge that has been gained, including depicting what lessons have been learnt.